Possíveis impactos econômicos do milho opaco-2 na nutrição humana e animal - F Patrick, George; Batista de Oliveira, Evonir; Leitão e Silva, Josué; Melgaço A Costa, Paulo (Revista Ceres, 2025)
The present study is an economic analysis oftwo feeding experiments realizes at the UFV with opaque-2 corn in the growing and finishing ration for swine. Tabular analysis was used in the analysis.